Development Strategy of SMEs Perca Crafts in Bogor City - Ali Alfaraesy; Etin Indrayani; Ahmad Averus Toana (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
The increase in the number of Small & Medium-Sized Enterprises (SMEs) in Bogor City is not in accordance with Economic Growth according to GRDP and increased employment opportunities in Bogor City. Goverment Regulation of Bogor City Number 4 of 2021 concerning Empowerment, Development and Protection of Cooperatives and Micro Enterprises in the City of Bogor aims to grow and develop businesses in the context of developing the regional economy, especially employment opportunities for the community while simultaneously encouraging domestic production in Bogor City. Perca craft SMEs Center is a community business in Bogor City that has potential because it is considered capable of playing a role in improving and restoring the community's economy, creating new jobs, alleviating poverty and sports which are still crucial problems in the area and empowering the community. environment by utilizing waste (used cloth) from the convection business that can be utilized into products that have high value and selling power. The purpose of this study was to describe the internal and external factors faced by perca craft SMEs, describe the development strategy for perca craft SMEs and determine priority strategies in the development of perca craft SMEs in Bogor City. This research uses a descriptive qualitative research method by collecting data in the form of interviews, documentation and observations using SOAR analysis (strengths, opportunities, aspirations, and results) which then produces alternative strategies which will be prioritized according to the main strategy using the litmust test. The results of this study indicate a strategy that can be implemented in the development of MSMEs in patchwork craftsmen, namely expanding the market network with several shopping centers in the city of Bogor and outside the city of Bogor and always participating in regional, national and even international events, then maximizing social media and e-commerce. commerce in its online promotion as a whole e-commerce that can be accessed by all people so that patchwork products are increasingly recognized by the public and can even go-international and collaborate with pentahelix which was built with various parties/stakeholders in its development to become a strong and independent MSME role in improving the community's economy by optimizing the potential of sustainable local resources.